Analisa Metode AHP Pada Minat dan Bakat Siswa SMA dalam Memilih Jurusan Pada Perguruan Tinggi Di Aceh Tengah - Zulfa, Ira; S, Richasanty Septima; A, Auliadi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The AHP (Analytical Hierarchy Process) method is suitable for the decision making process because it can determine scores for each different criteria, then proceed with the best alternative selection process. In the SPK (decision support system) is used web-based that can be accessed anytime, anywhere. So that at school, high school students (high school) can access the system through the school's computer. Requirements analysis is divided into 2 types, namely functional requirements (Functional Requirements) are types of requirements that contain the processes that will be carried out by the system and non-functional requirements (Non Functional Requirements) are types of requirements that contain behavioral properties owned by the system. Criteria for test results is a requirement for decision makers in determining the selection of study programs in Higher Education, based on the DAT test, the results of which are divided into 3 criteria, namely verbal ability, numerical ability, and spatial ability. Of the 100% accuracy of the results on the system using the AHP method in this system only results in 75% of the accuracy of the results.